Comparison of Flutter and Autogenic Drainage on Airway Clearance In Patients with Moderate Chronic Bronchitis.: Life Sciences-Physiotherapy for Better Pain Management - Dr. Chandrakant B Patil; Dr. Javid H Sagar (International Journal of Life Science and Pharma Research, 2022)
Patients with COPD have large amount of secretions. Many conventional and advanced techniques are used to clear the respiratory secretions. Flutter device is a hand held device which works on principle of positive expiratory pressure to improve patient’s ability to eliminate excessive secretions. Autogenic drainage is a self-drainage technique used for controlled breathing and moving excessive secretions. There is paucity of literature about this newer techniques used for chest clearance in moderate chronic bronchitis, so the present study is conducted with aim to find the effect of autogenic drainage and flutter device for airway clearance in individuals with moderate chronic bronchitis. A Comparative study was conducted on 30 subjects selected as per inclusion and exclusion criteria and divided into 2 groups by convenient sampling method. Group A was treated with flutter device and Group B by autogenic drainage technique. The treatment duration was 30 minutes per session, 2 sessions per day, 5 days/week for 1 week. The outcome measures used was oxygen saturation, peak expiratory flow rate and rate of perceived exertion on Borg scale. At the end of 1 week, both groups showed improvement in pre post values within group but between group comparison we found statistically significant improvement in group A (Flutter device) than Group B (autogenic drainage). The SpO2 value showed appreciable significant improvement in group A than group B (p=0.0066). The rate of perceived exertion showed extremely significant improvement in group A than group B (p<0.0001). The peak expiratory flow rate showed statistically significant improvement in group A than group B (p=0.0004).The study concluded that though both the techniques is better for airway clearance in chronic bronchitis but flutter device is more effective than autogenic drainage.